Pengaruh Model Pembelajaran Inside Outside Circle (IOC) Terhadap Hasil Belajar IPA - ni made sepria utami; ni nyoman kusmariatni; ndara tanggu renda (Universitas Pendidikan Ganesha, 2018)
This study was aimed to determine the differences between of the science learning outcomes of students who take the learning to Inside Outside Circle model with students who take the conventional learning of the fifth grade of SD Cluster III, Jembrana Subdistrict, Jembrana Regency in the academic year 2017/2018. The study was quasi-experimental. The population of this study was the all of the students that was 149 students in the fifth grade of of SD Cluster III, Jembrana Subdistrict, Jembrana Regency in the academic year 2017/2018. The Samples of this research are students of class V SDN 2 Dauhwaru, which amounted to 20 students and students of class V SDN 4 Dauhwaru, which amounted to 25 students. Science student learning outcomes data collected by multiple choice tests. Data collected were analyzed using descriptive statistics analysis and inferential statistics (t-test). Judging from the t-test results obtained t count = 3,06 and t table (db = 50 at a significance level of 5%) = 2,021. It is means that tcount>t table, while the result of the average calculation science learning outcomes that learning to Inside Outside Circle model is 19,35 greater than that learned with the conventional learning is 15,32. It means that inside Outside Cicrle model has an effect of students’ achievement in science lesson in the 5th Grade of SD Cluster III, Jembrana Subdistrict, Jembrana Regency in the academic year 2017/2018.